Teacher leadership for organizational change - Damkuvienė, Milda (Array, 2019)
The aim of this article is to test the teacher leadership initiated by teacher professional development abroad, as a factor of organisational change in a structural equation model. Structural equation modelling was employed to analyse survey data collected from 218 teachers who participated in professional development activities abroad under Erasmus+ KA1 in 32 Lithuanian schools. The model expresses the relationship between teacher leadership and organizational change, where teacher professional development abroad is treated as an initial (self-development) dimension of teacher leadership. Results revealed the positive and significant relationship between teacher leadership and organizational change, where leadership is conceptualized as an ongoing relational process of selfdevelopment, dispersing ideas, involving others and gaining commitment. Findings of the study also depicted a positive and significant relationship of didactic competence (the dimension of self-development phase of leadership) with one of the dimensions of organizational change - learning in the classroom.